ASURANSI DALAM PERSPEKTIF ISLAM - Aravik, Havis (Universitas Islam Negeri Raden Fatah Palembang, 2016)
This article discusses how insurance aplikable in Islam perspective. The results of discussion is that insurance as Islamic Economic (muamalah) practice today, is not known at the time of the Prophet Muhammad, so that the legal basis textually not found in the Quran and hadith, the results of previous scholars and ijtihad in codes of Islamic Law. Islamic insurance which is being developed today, can essentially reduce the burden and narrowness, and bring benefits in people's lives. Therefore, the community should begin to see the prospect of such insurance as the media to protect themselves from the various possibilities of unwanted later, while participating together help each other in goodness and piety.